The Educational and Communication Aspects of Using the Internet in the Context of the Young Generation - Małgorzata Papier (Lubelski Rocznik Pedagogiczny, 2018)
The article informs about important part of information society – using of Internet in education. In the last years, we face with misusing of the Internet by young people. This abuse effect is researched. The indisputable fact is attendance of media in education. Therefore, it is important and essential to point out the advantages as well as the risks, which are related to use of the Internet in many life areas. There should be a tendency to make the network users aware that the Internet activities could be planned and advised. In the article, an educational function of the Internet and the issue of the change of Internet communication among the young generation were presented. The theory connected with the research results relating to information society demonstrates chances and dangers for future education of “digital native” generation.